A cost-effective method for recycling carbon and metals in plants: synthesizing nanomaterials. Issue 2 (3rd January 2017) - Liu, Haiyang; Ren, Miao; Qu, Jiao; Feng, Yue; Song, Xiangmeng; Zhang, Qian; Cong, Qiao; Yuan, Xing
Abstract : This work focuses on the synthesis of nanomaterials, including multi-walled carbon nanotubes (MWCNTs), nanoparticles and nanocomposites, using the shoots of Sedum alfredii Hance and Brassica juncea L. (collected from a Cu–Zn mine area) as raw materials. Abstract : This work focuses on the synthesis of nanomaterials, including multi-walled carbon nanotubes (MWCNTs), nanoparticles and nanocomposites, using the shoots of Sedum alfredii Hance and Brassica juncea L. (collected from a Cu–Zn mine area) as raw materials. The vascular bundles in S. alfredii and B. juncea turned into MWCNTs through a heating–cooling process after the metals in them were extracted with H2 SO4 and formed sulfate which then reacted with OH − to synthesize metallic oxide nanoparticles. In addition, the nanoparticles were precipitated on the surface of the MWCNTs and formed MWCNT–metallic oxide nanocomposites. It was found that the structures of all MWCNTs from S. alfredii and B. juncea were middle-hollow. Their inner and outer diameters were 20 and 80 nm from S. alfredii and 60 and 80 nm from B. juncea, respectively. The ZnO nanoparticles, synthesized from S. alfredii, were nonuniform with a diameter around 30 nm and the Cu/ZnO nanoparticles, synthesized from B. juncea, corresponded to a Cu0.05 Zn0.95 O structure. Both ZnO and Cu0.05 Zn0.95 O nanoparticles, coated onto the surfaces of the MWCNTs, were nonuniform and agglomerated, with an outer diameter around 100 nm. There were no impurities existing in the synthesized nanomaterials. The reproducibility of the synthesized nanomaterials using both S. alfredii and B. juncea was high and stable. The yields of the synthesized nanomaterials using one plant of S. alfredii or B. juncea were 501.3 ± 364.2 mg and 637.5 ± 284.4 mg for the MWCNTs, 120.8 ± 59.3 mg for the ZnO nanoparticles and 145.1 ± 43.2 mg for the Cu0.05 Zn0.95 O nanoparticles, and 592.7 ± 164.7 mg for the MWCNT–ZnO nanocomposites and 711.5 ± 327.5 mg for the MWCNT–Cu0.05 Zn0.95 O nanocomposites, respectively. The cost for synthesis of 1 kg of MWCNTs was around US 120 using S. alfredii or B. juncea .